2012
DOI: 10.1380/ejssnt.2012.463
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations for Shave-Off Profiling

Abstract: Shave-off profiling with nano-beam SIMS achieves the highly precise depth profiling with nanometer-scaled depth resolution by utilizing FIB micro-machining process to provide depth profile. This method has its own features: absolute depth scale, pin point depth profiling and application to rough surface and/or hetero interface. However, the discussion of the sputtering mechanism in shave-off profiling is still insufficient because shave-off scan mode has distinctive position of the primary ion beam against the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…It could be calculated 2.22 × 10 13 atoms and 2.88 × 10 13 atoms, the results implied that the shave-off scan mode has 1.3 times higher sputtering yield compared with raster scan mode at the same beam condition. This ratio almost agreed with our previously reported results (shave-off scan sputtering yield: 3.6 atoms/ion, raster scan sputtering yield: 2.79 atoms/ion)[3].…”
supporting
confidence: 93%
“…It could be calculated 2.22 × 10 13 atoms and 2.88 × 10 13 atoms, the results implied that the shave-off scan mode has 1.3 times higher sputtering yield compared with raster scan mode at the same beam condition. This ratio almost agreed with our previously reported results (shave-off scan sputtering yield: 3.6 atoms/ion, raster scan sputtering yield: 2.79 atoms/ion)[3].…”
supporting
confidence: 93%
“…Using these techniques, the shave‐off depth resolutions were estimated to be approximately 20 nm . On the other hand, the mixing effects of the primary ion bombardment using the shave‐off scan mode were investigated using molecular dynamics simulations, and results suggested that the mixing effect under the shave‐off scan mode was small. Compared with the shape of the cross section, this mixing effect (thickness of mixing layer) has the potential to be a very important factor for the estimation of the depth resolution under the shave‐off condition.…”
Section: Introductionmentioning
confidence: 99%